Global Gene Expression and Pathway Analysis of Liver Obtained After 8 and 16 Weeks of Feeding Soy Isolate- or Casein-Based Diets in Male Obese Zucker Rats. (29th May 2020) - Kozaczek, Melisa; Bottje, Walter; Greene, Elizabeth; Lassiter, Kentu; Kong, Byungwhi Caleb; Rochelle, Sam; Dridi, Sami; Albataineh, Diyana; Hakkak, Reza
Abstract: Objectives: To understand how soy protein isolate (SPI) reduced liver steatosis in male obese Zucker rats, we conducted global gene expression (RNAseq) analysis on liver samples of male rats fed either the SPI or a control casein (CAS)-based diet (n = 8 per group) for 8 or 16 weeks. Methods: Data was analyzed using Ingenuity Pathway Analysis (IPA) software (Qiagen, CA) using a P < 0.05 and 1.3 fold differential expression cutoff values. Results: Out of 12 top differentially expressed genes (both up- and down-regulated) that were listed at either 8 or 16 wks of feeding (24 total), only the expression of one gene exhibited a reversal (from down-regulated to up-regulated) between 8 and 16 wks indicating consistency in the liver steatosis model. An assessment of diseases and functions based on differentially expressed target molecules in the dataset revealed that lipid metabolism was predicted to be enhanced at 16 wks whereas inflammatory response was predicted to be inhibited in SPI-fed compared to CAS-fed rats at both 8 and 16 weeks. Using the upstream regulator analysis and regulator effects functions of the IPA program enables the prediction of a number of upstream regulators (e.g., transcription regulators) that could be playing important roles in attenuating or promoting liver steatosis due to SPI or CAS diets. Examples of upstream regulators that were predicted to be activated (based on expression of down-stream target molecules) that were linked to increased conversion of lipid and transport of lipid in SPI-fed rats included hepatocyte nuclear factor 4 alpha and aryl hydrocarbon receptor. Examples of upstream regulators that were predicated to be activated in CAS-fed rats that were linked to predicted activation of phagocytosis and neutrophil chemotaxis included colony stimulating factor 2 and tumor necrosis factor. Conclusions: We believe these findings may shed light on mechanisms that SPI is able to reduce liver steatosis in this obese Zucker rat model. Funding Sources: Arkansas Bioscience Institute and U of A Chancellor Innovative Fund.